Pediatric Poisoning in Egypt - Aisha Ibrahim Maklad, Ashraf Mahmoud Emara, Enas Ibrahim El-Maddah, Mennat-Allah Ahmed Mahmoud El-Refai (Journal of Applied Pharmaceutical Science)
Poisoning exposures are a widespread public health problem for children and represents one of the most common medical emergencies encountered in young children, and accounts for a significant proportion of emergency room visits for the adolescent population. The aim of this work is to collect data for management of the most common pediatric poisoning in Egypt as a guideline for physicians and toxicologists. Most common childhood ingestions involve nontoxic substances or nontoxic doses of potentially toxic drugs or products, although a few ingestions can be very dangerous and require treatment. There are three things that typically put children at risk for toxic ingestion: improper storage of substances in the home, children spending more time in other people's homes, and caregiver distraction. The majority of exposures is accidental and occurs in children under the six years of age. The pediatric population is a very dynamic group because the physiologic processes that determine drug disposition undergo rapid changes as children grow, these pharmacokinetic properties, change as children mature with the most dramatic changes occurring in the first year of life. Most common pediatric poisoning in Egypt include insecticides, corrosives, hydrocarbons, food poisoning, analgesics, antihistamines, carbamazepines, phenol and oral contraceptive pills. Assessment of an acutely poisoned child involves the taking of an appropriate history, assessment of the level of consciousness, ventilation and circulation, a physical examination, and requesting appropriate toxicological and non-toxicological investigations. When a child presents with suspected poisoning, begin with an assessment of the airway, breathing and circulation. Activated charcoal is a universal antidote for the majority of poisons. Antidotes are playing an increasing role in therapy for pediatric poisonings. Poison prevention should continue as an integral part of anticipatory guidance activities of infant and child health care providers.
Keywords: Poison center, infant and child, poisoning, assessment.